The Role of Mitochondrial ATP-Sensitive Potassium Channels in Cardioprotective and Anti-Inflammatory Effects of Troxerutin in Myocardial Reperfusion Injury: Mitochondrial ATP-sensitive Potassium Channel as Target of Troxerutin in Cardioprotection - Mokhtari, Behnaz; Masoud, Farid; Javadi, Aniseh; Badalzadeh, Reza (Iranian Journal of Pharmaceutical Sciences, 2022)
A major clinical challenge in ischemic heart disease is the prevention of myocardial injury following ischemia/reperfusion (I/R). Application of natural pharmaceuticals seems to be clinically interesting due to their multiplex activities. Protective effects of troxerutin (TXR) in myocardial I/R injury have been ever demonstrated, nevertheless, the purpose of this study is to explore the role of mitochondrial adenosine triphosphate -sensitive potassium (mitoKATP) channels and toll-like receptor 4 (TLR4)-nuclear factor kappa B (NF-κB) pathway in cardioprotective effects of TXR against I/R injury in rats. Male Wistar rats (n=72, 250–300 g, 12 weeks old) were randomized into groups with/without I/R and/or TXR and 5-hydroxydecanoate (5-HD), alone or in combination. To induce I/R model, the langendorff-perfused hearts were subjected to left anterior descending coronary artery (LAD) ligation and re-opening. TXR (150mg/kg/day) was administered for 4 weeks before I/R. Moreover, 5-HD (100 µM) was added to the perfusion solution before the ischemia. Finally, myocardial infarct size, LDH release, protein expression levels of TLR4 and NF-κB, and the levels of pro-inflammatory cytokines (TNF-α and IL-1β) were assessed. TXR preconditioning significantly reduced IS and LDH release (P<0.05). Furthermore, it decreased the expression of TLR4 and NF-κB and the level of pro-inflammatory cytokines (P<0.05 to P<0.01). Inhibition of mitoKATP channels by 5-HD significantly reversed the cardioprotective effects of TXR. This work shed some light on the knowledge about the mechanisms involved in the anti-inflammatory effect of TXR preconditioning in myocardial I/R injury. This effect may be partly mediated through mitoKATP channels opening and subsequent suppression of the TLR4/NF-κB pathway.